Thiamine, Ascorbic Acid, and Hydrocortisone As a Metabolic Resuscitation Cocktail in Sepsis: A Meta-Analysis of Randomized Controlled Trials With Trial Sequential Analysis*. Issue 12 (December 2021) - Assouline, Benjamin; Faivre, Anna; Verissimo, Thomas; Sangla, Frédéric; Berchtold, Lena; Giraud, Raphaël; Bendjelid, Karim; Sgardello, Sebastian; Elia, Nadia; Pugin, Jérôme; de Seigneux, Sophie; Legouis, David
Abstract : OBJECTIVES: Sepsis is a common condition in the ICU. Despite much research, its prognosis remains poor. In 2017, a retrospective before/after study reported promising results using a combination of thiamine, ascorbic acid, and hydrocortisone called "metabolic resuscitation cocktail" and several randomized controlled trials assessing its effectiveness were performed. DESIGN: We conducted a systematic review and meta-analysis of randomized controlled trials in septic ICU patients to assess the effects of this combination therapy. SETTING: PubMed, Embase, and the Cochrane library databases were searched from inception to March of 2021. Data were extracted independently by two authors. The main outcome was the change in Sequential Organ Failure Assessment score within 72 hours. Secondary outcomes included renal composite endpoints (acute kidney injury) Kidney Disease - Improving Global Outcome organization stage 3 or need for renal replacement therapy, vasopressor duration, and 28-day mortality. SUBJECTS: We included randomized controlled trials with patients admitted to the ICU with sepsis or septic shock. INTERVENTION: The trials compared a combination of thiamine, ascorbic acid, and hydrocortisone to standard care or placebo in patients admitted to ICU with sepsis or septic shock. MEASUREMENTS AND MAIN RESULTS: We included eight randomized controlled trials ( n = 1, 335 patients). Within 72 hours, the median of mean improvement was –1.8 and –3.2 in the control and intervention groups, respectively (eight randomized controlled trials, n = 1, 253 patients); weighted mean difference –0.82 (95% CI, –1.15 to –0.48). Data were homogeneous and the funnel plot did not suggest any publication bias. Duration of vasopressor requirement was significantly reduced in the intervention group (six randomized controlled trials). There was no evidence of a difference regarding the ICU mortality and the renal composite outcome (acute kidney injury KDIGO 3 or need for renal replacement therapy, seven randomized controlled trials). CONCLUSIONS: Metabolic resuscitation cocktail administrated in ICU septic patients improves change in Sequential Organ Failure Assessment score within 72 hours. However, this improvement is modest and its clinical relevance is questionable. The impact on renal failure and mortality remains unclear. Abstract : Supplemental Digital Content is available in the text.